Peningkatan Kompetensi dan Produktivitas Karyawan 86 Production melalui Program Pelatihan DreamCamp 2025 - Muhammad Muzakky Abd Harits; Arief Budiman (POTENSI: Jurnal Pengabdian Masyarakat Ekonomi dan Bisnis, 2025)
The Event Organizer (EO) industry is experiencing very rapid development, and human resource capabilities are a determining factor in competition. 86 Production, a company in the EO sector, realized the need to improve employee capabilities and launched the DreamCamp training program. This program includes socialization of event flow and performance techniques, kick off of the company's target program, and team building. The implementation of DreamCamp, which is a training for employees and freel ancers of 86 Production, took place at the Kusuma Agrowisata Resort & Convention Hotel, Batu, East Java. This program was attended by 50 participants and the 86 Production internship team as the organizer. The results of this program showed high enthusiasm and participation from the participants, as evidenced by the activeness of the participants during the material session, pretest-posttest which showed increased understanding, and appreciation for the best participants. This program also includes a kick off program in the form of company targets for next year and team building to improve team collaboration. However, there were obstacles in the form of increasing the duration of the material presentation which had an impact on the next agenda. Overall, DreamCamp was considered successful in increasing knowledge and collaboration potential. However, further evaluation is needed to improve time management and operational readiness. Industri Event Organizer (EO) telah mengalami pengembangan yang cepat, dan kemampuan sumber daya manusia adalah faktor penting dalam persaingan. 86 Production, sebuah perusahaan dibidang EO, telah mengidentifikasi kebutuhan untuk meningkatkan kemampuan karyawan dan meluncurkan program pelatihan DreamCamp. Program ini mencakup sosialisasi flow event dan teknis kinerja, kick off program target perusahaan dan team building. Pelaksanaan DreamCamp yang berupa pelatihan karyawan dan pekerja lepas 86 Production berada di Kusuma Agrowisata Resort & Convention Hotel, Batu, Jawa Timur. Program ini dihadiri oleh 50 peserta dan tim magang 86 Production sebagai penyelenggara. Hasil program menunjukkan antusiasme dan partisipasi tinggi peserta, yang dibuktikan dengan keaktifan peserta selama sesi materi, pretest-posttest yang mengindikasikan peningkatan pemahaman, dan apresiasi peserta terbaik. Program ini juga mencakup kick off program berupa tujuan perusahaan untuk tahun depan dan team building untuk meningkatkan kolaborasi tim. Meskipun demikian, terdapat kendala berupa bertambah panjangnya waktu pemaparan materi yang mempengaruhi pada agenda berikutnya. Secara keseluruhan, DreamCamp dianggap berhasil meningkatkan pengetahuan dan potensi kolaborasi. Namun, evaluasi lebih lanjut diperlukan untuk meningkatkan manajemen waktu dan kesiapan operasional.